High-transparency photocatalytic film as well as preparation method and application thereof
By using PMMA matrix and CdxZn1-xS nanoparticles in the photocatalytic film, the dispersion of nanoparticles and the film preparation process are optimized, and the problems of nanoparticle agglomeration and film inhomogeneity are solved, and high transparency and high efficiency photocatalysis are achieved.
Patent Information
- Application Number
- CN202411379386.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
AI Technical Summary
Existing zinc-cadmium sulfide nanoparticles are prone to agglomeration in solution, resulting in uneven distribution in the matrix, affecting the photocatalytic efficiency, and at the same time, high transparency is needed to improve the photocatalytic efficiency.
A high-transparency photocatalytic film was prepared using polymethyl methacrylate (PMMA) matrix and CdxZn1-xS nanoparticles. By optimizing the dispersion of nanoparticles and the preparation process of the film, the uniform distribution of nanoparticles in the film was achieved.
It significantly improves the photocatalytic efficiency, overcomes the problems of nanoparticle agglomeration and film inhomogeneity, while maintaining high transparency, and has broad application prospects.
Smart Images

Figure CN119406457A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic films, and in particular to a high-transparency photocatalytic film and a preparation method and application thereof. Background Art
[0002] Photocatalytic technology has important applications in environmental governance and clean energy. x Zn 1-x S, where 0.1≤x≤0.9) is a semiconductor material with excellent photocatalytic performance and has attracted much attention due to its adjustable wide band gap, high light absorption efficiency and good chemical stability. x Zn 1-x S nanoparticles can optimize their light absorption performance and photocatalytic activity by changing the ratio of zinc and cadmium, and are suitable for a variety of photocatalytic reactions. However, nanoparticles tend to agglomerate in solution, resulting in uneven distribution in the matrix, which in turn affects the photocatalytic efficiency.
[0003] The transparent photocatalytic film based on zinc cadmium sulfide needs to maintain good transparency while improving the photocatalytic efficiency to ensure that zinc cadmium sulfide efficiently receives light sources. When the light transmittance of the film increases, the photocatalytic efficiency can be effectively improved. Therefore, it is of great significance to prepare a catalytic film with high light transmittance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-transparency photocatalytic film and its preparation method and application, using polymethyl methacrylate (PMMA) matrix and Cd x Zn 1-x S nanoparticles are used to prepare high-transparency photocatalytic films. By optimizing the dispersion of nanoparticles and the preparation process of the film, the uniform distribution of nanoparticles in the film is achieved, overcoming the problems of nanoparticle agglomeration and film unevenness. The PMMA-based photocatalytic film not only has high transparency, but also significantly improves the photocatalytic efficiency by improving the dispersion of nanoparticles and the uniformity of the film. This provides a new idea for the preparation of films with excellent photocatalytic properties and high transparency, and has broad application prospects.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a high-transparency photocatalytic film, comprising the following steps:
[0006] S1, dissolving thiourea, cadmium acetate dihydrate and zinc acetate dihydrate in deionized water, and performing a hydrothermal reaction to obtain cadmium zinc sulfide nanoparticles;
[0007] S2, immersing the glass slide cured with the polymethyl methacrylate film into a zinc cadmium sulfide nanoparticle solution, wherein the polymethyl methacrylate film adsorbs the zinc cadmium sulfide nanoparticles;
[0008] S3, drying the polymethyl methacrylate film adsorbed with zinc cadmium sulfide nanoparticles to obtain the high-transparency photocatalytic film.
[0009] The invention prepares zinc cadmium sulfide nanoparticles through the hydrothermal reaction of thiourea, cadmium acetate dihydrate and zinc acetate dihydrate, and immerses a glass slide cured with a polymethyl methacrylate film into a solution of the zinc cadmium sulfide nanoparticles, so that the zinc cadmium sulfide nanoparticles are uniformly adsorbed on the polymethyl methacrylate film, and after drying, a high-transparency photocatalytic film based on a PMMA matrix of the zinc cadmium sulfide nanoparticles is obtained; the process method is simple, and the problems of easy agglomeration of the zinc cadmium sulfide nanoparticles in the matrix solution and uneven film thickness are solved; the obtained photocatalytic film has excellent light transmittance, and simultaneously exhibits excellent catalytic activity in the process of photocatalytic hydrogen evolution, and has broad application prospects.
[0010] Furthermore, the solvent of the zinc cadmium sulfide nanoparticle solution is deionized water, the mass concentration of the zinc cadmium sulfide nanoparticles is 10%, and the immersion time is 10-60 minutes.
[0011] Furthermore, the ratio of the molar number of thiourea to the total molar number of cadmium acetate dihydrate and zinc acetate dihydrate is 1:(1-4), and the molar ratio of cadmium acetate dihydrate to zinc acetate dihydrate is (1-9):(1-9).
[0012] Furthermore, the particle size of the zinc cadmium sulfide nanoparticles is 5-20 nm.
[0013] Furthermore, in S2, the preparation method of the glass slide cured with the polymethyl methacrylate film is: coating a polymethyl methacrylate solution with a concentration of 10-15wt% on the glass slide, and curing it at 40-60°C for 0.5-2h.
[0014] Furthermore, the solvent of the polymethyl methacrylate solution is acetone or N,N-dimethylformamide (DMF).
[0015] Further, in S3, the drying process comprises the following steps:
[0016] (1) drying the polymethyl methacrylate film adsorbed with zinc cadmium sulfide nanoparticles naturally at room temperature;
[0017] (2) The film naturally dried in step (1) is heated to 60-85°C at a rate of 4-6°C / min and kept dry for 0.5-2h.
[0018] Furthermore, the thickness of the high-transparency photocatalytic film is 1-5 μm.
[0019] Furthermore, in S1, the concentrations of cadmium acetate dihydrate and zinc acetate dihydrate are independently selected from 0.01-0.1M, and the concentration of thiourea is 0.05-0.2M.
[0020] Furthermore, in S1, the temperature of the hydrothermal reaction is 140-160° C., and the time is 12-24 hours.
[0021] The second aspect of the present invention provides a high-transparency photocatalytic film prepared by the preparation method described in the first aspect.
[0022] The third aspect of the present invention provides application of the high-transparency photocatalytic film described in the second aspect in the field of photocatalytic hydrogen evolution.
[0023] Beneficial effects of the present invention:
[0024] The invention prepares zinc cadmium sulfide nanoparticles through the hydrothermal reaction of thiourea, cadmium acetate dihydrate and zinc acetate dihydrate, and immerses a glass slide cured with a polymethyl methacrylate film into a solution of the zinc cadmium sulfide nanoparticles, so that the zinc cadmium sulfide nanoparticles are uniformly adsorbed on the polymethyl methacrylate film, and after drying, a high-transparency photocatalytic film based on a PMMA matrix of the zinc cadmium sulfide nanoparticles is obtained. The process method is simple, and the problems of easy agglomeration of the zinc cadmium sulfide nanoparticles in the matrix solution and uneven film thickness are solved.
[0025] The photocatalytic film prepared by the method of the present invention has excellent light transmittance and exhibits excellent catalytic activity in the process of photocatalytic hydrogen evolution, and has broad application prospects.
[0026] The photocatalytic film prepared by the method of the present invention has uniform thickness, which overcomes the problem of uneven thickness of the photocatalytic film and ensures the consistency of photocatalytic performance of various regions of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a process flow chart of the preparation of the high-transparency photocatalytic film of the present invention;
[0028] Figure 2 is a schematic diagram of the preparation of zinc cadmium sulfide nanoparticles of the present invention;
[0029] Explanation of the numbers in the figure: 1. glass slide cured with polymethyl methacrylate film, 11. polymethyl methacrylate film, 2. zinc cadmium sulfide nanoparticle solution, 21. zinc cadmium sulfide nanoparticles, 4. high transparency photocatalytic film. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0031] The present invention provides a method for preparing a high-transparency photocatalytic film. Figure 1 As shown, the following steps are included:
[0032] (1) Thiourea, cadmium acetate dihydrate and zinc acetate dihydrate are mixed and dissolved in deionized water DI, and subjected to hydrothermal reaction to obtain zinc cadmium sulfide nanoparticles, such as Figure 2 As shown;
[0033] (2) immersing a glass slide 1 having a polymethyl methacrylate film cured thereon into a zinc cadmium sulfide nanoparticle solution 2, wherein the polymethyl methacrylate film 11 adsorbs the zinc cadmium sulfide nanoparticles 21;
[0034] (3) Drying the polymethyl methacrylate film 11 adsorbed with the zinc cadmium sulfide nanoparticles 21 to obtain the high-transparency photocatalytic film 3.
[0035] Specifically, in S1, the ratio of the molar number of thiourea to the total molar number of cadmium acetate dihydrate and zinc acetate dihydrate is 1:(1-4), and the molar ratio of cadmium acetate dihydrate to zinc acetate dihydrate is (1-9):(1-9). The concentrations of cadmium acetate dihydrate and zinc acetate dihydrate are independently selected from 0.01-0.1M, and the concentration of thiourea is 0.05-0.2M. The temperature of the hydrothermal reaction is 140-160°C, and the time is 12-24h. The solvent of the zinc cadmium sulfide nanoparticle solution is deionized water, the mass concentration of the zinc cadmium sulfide nanoparticles is 10%, the immersion time is 10-60min, and the particle size of the zinc cadmium sulfide nanoparticles is 5-20nm.
[0036] Specifically, in S2, the preparation method of the glass slide cured with a polymethyl methacrylate film is: coating a polymethyl methacrylate solution with a concentration of 10-15wt% on the glass slide, and curing it at 40-60°C for 0.5-2h; the solvent of the polymethyl methacrylate solution is acetone or N,N-dimethylformamide (DMF).
[0037] Specifically, in S3, the drying treatment comprises the following steps: (1) drying the polymethyl methacrylate film adsorbed with zinc cadmium sulfide nanoparticles at room temperature; (2) heating the film after natural drying in step (1) to 60-85°C at a rate of 4-6°C / min, and keeping the temperature for drying for 0.5-2h. The thickness of the high-transparency photocatalytic film is 1-5 μm.
[0038] Another embodiment of the present invention provides a high-transparency photocatalytic film prepared by the preparation method of the above embodiment.
[0039] Another embodiment of the present invention provides application of the high-transparency photocatalytic film of the above embodiment in the field of photocatalytic hydrogen evolution.
[0040] Example 1
[0041] In a 150 ml beaker, add 8 mmol of thiourea, 3 mmol of cadmium acetate dihydrate and 27 mmol of zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 9:1. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 160°C for 24 hours. After the reaction, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles with a particle size of 5-20 nm.
[0042] A glass substrate with a length of 5 cm × width of 2 cm × thickness of 0.2 mm was cleaned with acetone and an ultrasonic cleaner for 1 hour, and then cleaned with a 2wt% sodium hydroxide aqueous solution and an ultrasonic cleaner for 1 hour. After the surface of the substrate was dried, it was immersed in a 12wt% PMMA solution for 10 seconds. The substrate coated with the PMMA solution was pre-cured at 60°C for 30 minutes, and then immersed in a 10wt% aqueous solution of zinc cadmium sulfide nanoparticles for 15 minutes. After being taken out, it was naturally dried at room temperature, and then heated to 75°C at a heating rate of 5°C per minute, and continued to dry at this temperature for 1 hour, and finally a high-transparency photocatalytic film was obtained.
[0043] Example 2
[0044] In a 150 ml beaker, add 8 mmol of thiourea, 6 mmol of cadmium acetate dihydrate and 24 mmol of zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 8:2. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 150°C for 24 hours. After the reaction, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles with a particle size of 5-20 nm.
[0045] A glass substrate with a length of 5 cm × width of 2 cm × thickness of 0.2 mm was cleaned with acetone and an ultrasonic cleaner for 1 hour, and then cleaned with a 2wt% sodium hydroxide aqueous solution and an ultrasonic cleaner for 1 hour. After the surface of the substrate was dried, it was immersed in a 13wt% PMMA solution for 15 seconds. The substrate coated with the PMMA solution was pre-cured at 60°C for 40 minutes, and then immersed in a 10wt% aqueous solution of zinc cadmium sulfide nanoparticles for 20 minutes. After being taken out, it was naturally dried at room temperature, and then heated to 80°C at a heating rate of 5°C per minute, and continued to dry at this temperature for 1 hour, and finally a high-transparency photocatalytic film was obtained.
[0046] Example 3
[0047] In a 150 ml beaker, add 8 mmol of thiourea, 9 mmol of cadmium acetate dihydrate and 21 mmol of zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 7:3. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 140°C for 24 hours. After the reaction is completed, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles with a particle size of 5-20 nm.
[0048] A glass substrate with a length of 5 cm × width of 2 cm × thickness of 0.2 mm was cleaned with acetone and an ultrasonic cleaner for 1 hour, and then cleaned with a 2wt% sodium hydroxide aqueous solution and an ultrasonic cleaner for 1 hour. After the surface of the substrate was dried, it was immersed in a 14wt% PMMA solution for 20 seconds. The substrate coated with the PMMA solution was pre-cured at 60°C for 45 minutes, and then immersed in a 10wt% aqueous solution of zinc cadmium sulfide nanoparticles for 25 minutes. After being taken out, it was naturally dried at room temperature, and then heated to 80°C at a heating rate of 5°C per minute, and continued to dry at this temperature for 1 hour, and finally a high-transparency photocatalytic film was obtained.
[0049] Example 4
[0050] In a 150 ml beaker, add 8 mmol of thiourea, 12 mmol of cadmium acetate dihydrate and 18 mmol of zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 6:4. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 150°C for 24 hours. After the reaction is completed, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles with a particle size of 5-20 nm.
[0051] A glass substrate with a length of 5 cm × width of 2 cm × thickness of 0.2 mm was cleaned with acetone and an ultrasonic cleaner for 1 hour, and then cleaned with a 2wt% sodium hydroxide aqueous solution and an ultrasonic cleaner for 1 hour. After the surface of the substrate was dried, it was immersed in a 10wt% PMMA solution for 15 seconds. The substrate coated with the PMMA solution was pre-cured at 60°C for 30 minutes, and then immersed in a 10wt% aqueous solution of zinc cadmium sulfide nanoparticles for 20 minutes. After being taken out, it was naturally dried at room temperature, and then heated to 80°C at a heating rate of 5°C per minute, and continued to dry at this temperature for 1 hour, and finally a high-transparency photocatalytic film was obtained.
[0052] Example 5
[0053] In a 150 ml beaker, add 8 mmol of thiourea, 15 mmol of cadmium acetate dihydrate and 15 mmol of zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 5:5. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions of 160°C for 24 hours. After the reaction is completed, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles with a particle size of 5-20 nm.
[0054] A glass substrate with a length of 5 cm × width of 2 cm × thickness of 0.2 mm was cleaned with acetone and an ultrasonic cleaner for 1 hour, and then cleaned with a 2wt% sodium hydroxide aqueous solution and an ultrasonic cleaner for 1 hour. After the surface of the substrate was dried, it was immersed in a 15wt% PMMA solution for 20 seconds. The substrate coated with the PMMA solution was pre-cured at 60°C for 50 minutes, and then immersed in a 10wt% aqueous solution of zinc cadmium sulfide nanoparticles for 30 minutes. After being taken out, it was naturally dried at room temperature, and then heated to 85°C at a heating rate of 5°C per minute, and continued to dry at this temperature for 2 hours to finally obtain a high-transparency photocatalytic film.
[0055] Comparative Example 1
[0056] In a 150 ml beaker, add 8 mmol thiourea, 27 mmol cadmium acetate dihydrate and 3 mmol zinc acetate dihydrate, mix well to make a mother liquor, the molar ratio of zinc to cadmium in the solution is 1:9. Transfer the mother liquor to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 130°C for 24 hours. After the reaction is completed, wash the product with water and ethanol, separate it with a centrifuge, and dry it at room temperature to obtain zinc cadmium sulfide nanoparticles. Disperse the zinc cadmium sulfide nanoparticles in acetone to prepare a nanoparticle solution with a concentration of 10wt%.
[0057] Prepare PMMA solution: In a 150 ml beaker, add 10 g of PMMA and 90 ml of DMF (N,N-dimethylformamide), and stir on a magnetic stirrer until a uniform PMMA solution is formed.
[0058] The PMMA solution and the zinc cadmium sulfide nanoparticle solution were mixed in a volume ratio of 1:1, stirred evenly and poured into the syringe of the electrospinning machine. The voltage of the electrospinning machine was set to 20kV, the spinning distance was set to 15 cm, and the flow rate was set to 0.5 ml / hour. Electrospinning was performed on a cleaned and dried glass substrate to form a uniform nanofiber membrane. The spun glass substrate was naturally dried at room temperature for half an hour, and then calcined in a muffle furnace at 550°C for 1 hour. After calcination, it was taken out to obtain a PMMA photocatalytic film with zinc cadmium sulfide nanoparticles, and the final photocatalytic film was obtained.
[0059] Comparative Example 2
[0060] In a 150 ml beaker, add 5 mmol of tetraisopropyl titanate and 25 ml of ethanol. After sufficient stirring, transfer the mixture to a polytetrafluoroethylene-lined reaction vessel and react under hydrothermal conditions at 180 ° C for 12 hours. After the reaction is completed, the product is washed with water and ethanol, separated by a centrifuge, and dried at room temperature to obtain TiO2 nanoparticles. Subsequently, the TiO2 nanoparticles are mixed with 10 grams of PMMA, 90 ml of DMF (N, N-dimethylformamide) is added, and stirred on a magnetic stirrer until a uniform solution is formed. The solution is applied to a cleaned glass substrate and evenly coated by spin coating. After the solvent evaporates, it is calcined in a muffle furnace at 550 ° C for 1 hour to finally obtain a PMMA photocatalytic film with TiO2 nanoparticles.
[0061] The transmittance of the photocatalytic films prepared in the examples and comparative examples was tested. The ultraviolet absorbance of the obtained films was measured using an ultraviolet spectrophotometer at a wavelength of 300-480 nanometers. The transmittance was calculated according to the relationship: transmittance % = (1-ultraviolet absorbance) × 100%. The results are shown in Table 1.
[0062] Table 1
[0063] Group Light transmittance Example 1 93% Example 2 90% Example 3 89% Example 4 90% Example 5 87% Comparative Example 1 50% Comparative Example 2 50%
[0064] As can be seen from Table 1, the PMMA matrix loaded with zinc cadmium sulfide nanoparticles prepared by the method embodiments 1-5 of the present invention has a high transmittance, among which the transmittance of embodiment 1 is as high as 93%, which is conducive to the improvement of photocatalytic performance. The transmittance of the photocatalytic film prepared by electrostatic spinning after mixing zinc cadmium sulfide nanoparticles with PMMA spinning solution in comparative example 1 is greatly reduced, which is only 50%. This is because the zinc cadmium sulfide nanoparticles agglomerate in the spinning solution, resulting in uneven distribution in the matrix, thereby causing a decrease in transmittance, thereby affecting the photocatalytic performance. At the same time, the PMMA photocatalytic film with TiO2 nanoparticles in comparative example 2 also has a low transmittance.
[0065] The photocatalytic hydrogen evolution performance of the film was tested in a photocatalytic reaction device. The zinc cadmium sulfide nanoparticle-PMMA composite photocatalytic film prepared in Example 1 was weighed and placed in a transparent glass bottle with a capacity of 30 ml. Then 15 ml of ultrapure water was added to the bottle, and then Na2S / Na2SO3 (molar ratio 3.5:2.5) was added. The bottle mouth was sealed with a rubber stopper and squeezed and sealed with an aluminum-plastic cover. Finally, the reaction was carried out under visible light (420nm≤λ≤700nm) for 5 hours. After 5 hours, 2 ml of gas was extracted from the glass bottle using a 5 ml syringe and injected into a gas chromatograph to measure the hydrogen content. The hydrogen content was divided by the catalyst weight and the illumination time to obtain the photocatalytic hydrogen evolution rate. The photocatalytic hydrogen evolution rate of the photocatalytic film obtained in Example 1 was 2400 μmol / g / h. It can be seen that the photocatalytic film can be used for applications such as photocatalytic hydrogen evolution, and has excellent transparency and efficient photocatalytic performance.
[0066] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a high-transparency photocatalytic film, characterized in that: The steps include: S1, dissolving thiourea, cadmium acetate dihydrate and zinc acetate dihydrate in deionized water, and performing a hydrothermal reaction to obtain cadmium zinc sulfide nanoparticles; S2, immersing the glass slide cured with the polymethyl methacrylate film into a zinc cadmium sulfide nanoparticle solution, wherein the polymethyl methacrylate film adsorbs the zinc cadmium sulfide nanoparticles; S3, drying the polymethyl methacrylate film adsorbed with zinc cadmium sulfide nanoparticles to obtain the high-transparency photocatalytic film.
2. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: In S1, the ratio of the molar number of thiourea to the total molar number of cadmium acetate dihydrate and zinc acetate dihydrate is 1:(1-4), and the molar ratio of cadmium acetate dihydrate and zinc acetate dihydrate is (1-9):(1-9).
3. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: The particle size of the zinc cadmium sulfide nanoparticles is 5-20 nm.
4. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: In S2, the preparation method of the glass slide cured with the polymethyl methacrylate film is: coating a polymethyl methacrylate solution with a concentration of 10-15wt% on the glass slide, and curing it at 40-60°C for 0.5-2h.
5. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: In S3, the drying process comprises the following steps: (1) drying the polymethyl methacrylate film adsorbed with zinc cadmium sulfide nanoparticles naturally at room temperature; (2) The film naturally dried in step (1) is heated to 60-85°C at a rate of 4-6°C / min and kept dry for 0.5-2h.
6. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: The thickness of the high-transparency photocatalytic film is 1-5 μm.
7. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: In S1, the concentrations of cadmium acetate dihydrate and zinc acetate dihydrate are independently selected from 0.01-0.1M, and the concentration of thiourea is 0.05-0.2M.
8. The method for preparing a high-transparency photocatalytic film according to claim 1, characterized in that: In S1, the temperature of the hydrothermal reaction is 140-160°C and the time is 12-24h.
9. A high-transparency photocatalytic film prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high-transparency photocatalytic film according to claim 9 in the field of photocatalytic hydrogen evolution.